2013
DOI: 10.1007/s13566-013-0088-5
|View full text |Cite
|
Sign up to set email alerts
|

Report on revision of the Chinese 1992 staging system for nasopharyngeal carcinoma

Abstract: With the advances of diagnostic imaging and radiation therapy technology, the limitations of the Chinese 1992 staging system for nasopharyngeal carcinoma (NPC) become obvious, and the revision of this system was clearly needed. On December 16, 2008, the Chinese Committee for Staging of Nasopharyngeal Carcinoma (CCSNPC) was inaugurated in Guangzhou, China, with the purpose of establishing a platform for the study of the Chinese staging system and ensuring the continuity of the work of NPC staging research. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…However, several studies have found that the invasion rate of the hypopharynx, orbit, and cervical vertebra of NPC were very low 5,16,25,26. Based on the above results, the orbit and cervical vertebra were excluded in the Chinese system (2008 version) for NPC 27. Our research was consistent with the results of these studies.…”
Section: Discussionsupporting
confidence: 87%
“…However, several studies have found that the invasion rate of the hypopharynx, orbit, and cervical vertebra of NPC were very low 5,16,25,26. Based on the above results, the orbit and cervical vertebra were excluded in the Chinese system (2008 version) for NPC 27. Our research was consistent with the results of these studies.…”
Section: Discussionsupporting
confidence: 87%
“…The present study was approved by the Institutional Review Board of Nanfang Hospital (Guangzhou, China), and all patients provided written informed consent for the use of their imaging data. Staging was done using the 2008 nasopharyngeal carcinoma staging system in People's Republic of China (10). A summary of the patients' information is presented in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…Paranasal sinus invasion (PSI) occurs in ∼30% NPC patients (5), and yet, it has been controversial in its prognostic value. In the Chinese 2008 staging system for NPC, PSI was classified as T4 (6), but it was retained within the T3 category in the 8th edition of AJCC staging system (7). Recently, cumulating data through MRI-guided diagnosis and IMRT-based treatment revealed that T3 NPC with PSI have similar 5-year local recurrence-free survival (LRFS) and overall survival (OS) with T4 disease (8,9), suggesting the plausibility of further risk stratification within T3 classification.…”
Section: Introductionmentioning
confidence: 99%